Strategic Analysis the System of Long-term Management of Enterprise - Raikovska, I. T. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
The article is devoted research of role of strategic analysis in management system of enterprise with parallel determination ofchange of him rich in content filling, objects, article, tasks and subjects, in the context ofdevelopment of social-economic relations. On the basis of analysis of economic literature certainly, that a strategic analysis is, at first, by independent direction of analytical research, that occupies a leading place on each of the stages of strategic management an enterprise and envisages rich in content description of economic subject, exposure of features, tendencies, possible and impossible directions of its development for the sake of timely and adequate reaction on changes in the environment of its functioning andforming competitive edges that in a long-term prospect will provide increase of business cost, and, secondly, informative providing, as engulfs the results of actions of all other functions of management, is based on the facts of their display, redoes and reproduces new state information and its place activity of enterprise in an external environment for the sake of construction of strategy of continuity of activity of subject of menage. Differentiating of objects, article, tasks and subjects of strategic analysis, is offered after three forms of display as areas of scientific knowledges, educational discipline and practical activity, and certainly, that basic setting of strategic analysis as areas of scientific knowledges are providing of necessities ofpractice, that is why its article is an improvement and development of methodology. In accordance with the modern understanding of strategic analysis and for complete realization of his functions the ‘tree of tasks ” of strategic analysis activity of subject of menage with a purpose determination of order of organization and development of its method, construction of strategy of development of enterprise which will allow to form strategic thought of workers and provide efficiency and continuity of him economic activity is built.